They Must Be Wedded Frederick Ashton and the Royal Ballet - Jennings, Luke (Dance Books Ltd., Alton,Hampshire (UK), 2004)
PALABRAS CLAVE: Frederick Ashton, Royal Ballet, Kenneth MacMillan, A Wedding Bouquet, Requiem, Les Noces.